Taxonomy of the semiterrestrial crab Lepidothelphusa cognettii (Nobili, 1903) (Crustacea: Decapoda: Brachyura: Gecarcinucidae), with descriptions of five new species from Sarawak, Malaysia, Borneo - Jongkar, Grinang; K. L. Ng, Peter (Lee Kong Chian Natural History Museum, 2015)
The taxonomy of the semiterrestrial gecarcinucid crab Lepidothelphusa cognettii (Nobili, 1903) from Borneo is revised. The identity of L. cognettii s. str. is clarified and five new species: L. flavochela, L. limau, L. loi, L. padawan and L. sangon, are described from southwestern Sarawak, Malaysia. The species are characterised by their diagnostic live colours, structures of their carapaces, chelae, male abdomens and male first gonopods. They also occupy geographically discrete ranges, sometimes with different habitats.